Pengaruh Kebersyukuran dan Harga Diri terhadap Perilaku Konsumtif dalam Online Shopping melalui Platform Shopee pada Dewasa Awal di Sidoarjo - Natasya Dwi Clarita; Lely Ika Mariyati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The development of the internet, such as the Shopee platform, has facilitated access to online shopping, which has led to consumptive behavior in everyday life. This study aims to determine the influence of gratitude and self-esteem on consumptive behavior in online shopping through the Shopee platform among young adults in Sidoarjo. Using a quantitative method with a causal approach, this study involved 270 young adult respondents aged 18-25 years who were selected through purposive sampling. Data collection was conducted using three instruments, including a gratitude scale (12 items; α = 0.823), a Self-Esteem Scale (RSES) (10 items; α = 0.764), and a consumptive behavior scale (22 items; α = 0.865), all of which had been tested for validity and reliability. Data analysis was performed using multiple linear regression and Pearson's correlation using SPSS software. The results showed that the higher the level of gratitude and self-esteem possessed by individuals, the lower their consumptive behavior in online shopping. Thus, this study proves that there is a negative and significant influence between gratitude and self-esteem and consumptive behavior.